Perancangan HACCP di PT X dengan mempertimbangkan Peraturan Pemerintah tentang Antibiotic Growth Promoters (AGP) - Eliza Erlinda; Benedictus Rahardjo (Jurnal Titra, 2018)
The design of HACCP at PT X for animal feed is designed to identify the hazards present in the feed production process. This design also takes into account government regulations on the prohibition of the use of Antibiotic Growth Promoters. The method used in the design is Risk Assessment and FMEA. This method can identify the frequency and severity of hazards that can occur in the production process, the value and the risk level of the hazard. Hazards are categorized into four classes: low risk, moderate risk, high risk, dan very high risk. The result of the design is that there is no new danger due to the prohibition of the use of AGP. The hazards identified are significant not CCPs where hazards can be controlled with the OPRP Plan. Hazards that have the highest risk value is the water content is not standard in the pelletizing process with the risk value 6.